Caracterização molecular e genética da resistência de trigo à brusone conferida pela translocação 2NS/2AS - Vancini, Camila (2021)
Wheat is the second most produced cereal around the world, being fundamental in the food chain supply. Increasingly, alternatives are being sought to increase wheat yield and expand its cultivated area. Despite the wide wheat production, several adversities interfere this crop. One of the main problems in several producing regions is the incidence of wheat blast. This fungal disease is caused by the pathogen Magnaporthe oryzae and directly impairs grain production. Blast has a difficult control and genetic resistance is an efficient alternative to reduce the damage caused by the disease. The 2NS/2AS translocation has been widely studied and associated as the main source of wheat blast resistance. However, some genotypes carrying the 2NS fragment have shown variations, presenting a susceptibility phenotype. The present work had the following objectives: i) Study the inheritance of resistance conferred by the presence of 2NS translocation in F2 segregating wheat lines; and ii) Identify molecular markers that best explain the resistance phenotype conferred by the 2NS/2AS translocation. Therefore, two experimental approaches were developed. The first one was based on the genetic inheritance study of blast resistance, based on 2NS. It was carried out through the phenotyping of two F2 wheat segregating populations derived from crosses of parents contrasting for reaction to blast. The second was the molecular characterization of a wheat collection genotypes and characterization of two F2 segregating populations previously described. The F2 populations phenotyping showed that the inheritance of resistance conferred by 2NS can segregate in the 3R:1S ratio, suggesting a dominant effect gene controlling the resistance trait. However, this result may vary depending on the genetic background of the genotypes studied and the trait evaluated. The molecular characterization showed that all the markers used were efficient in differentiating resistant genotypes from those susceptible to wheat blast. Two markers stood out, displaying a significant difference between genotypes classified as resistant and susceptible for all phenotypic traits studied. Furthermore, the linkage disequilibrium analysis of the used markers indicated the presence of recombination in the 2NS/2AS translocation region. The results found in this study showed the potential of the 2NS/2AS translocation in genetic resistance to wheat blast and indicate that the resistance gene(s) to blast present in this translocation are dominant. Additionally, the results reinforce the variable “number of infection points in the rachis” as a trait of resistance to wheat blast and also indicate that M. oryzae sporulation has the potential to be used to evaluate wheat blast resistance.